2017
DOI: 10.3389/fphar.2017.00214
|View full text |Cite
|
Sign up to set email alerts
|

Vasorelaxing Action of the Kynurenine Metabolite, Xanthurenic Acid: The Missing Link in Endotoxin-Induced Hypotension?

Abstract: The kynurenine pathway of tryptophan metabolism is activated by pro-inflammatory cytokines. L-kynurenine, an upstream metabolite of the pathway, acts as a putative endothelium-derived relaxing factor, and has been hypothesized to play a causative role in the pathophysiology of inflammation-induced hypotension. Here, we show that xanthurenic acid (XA), the transamination product of 3-hydroxykynurenine, is more efficacious than L-kynurenine in causing relaxation of a resistance artery, but fails to relax pre-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…We also showed that commercial kynurenine relaxed pre-constricted arteries, which suggested that kynurenine is an endotheliumderived relaxant factor 6 . Although others have since confirmed these findings 11,12 , we noticed that recently purchased kynurenine no longer caused arterial relaxation, and that HPLC-purified kynurenine and NFK also failed to relax naïve mouse arteries (Fig. 1b).…”
mentioning
confidence: 56%
“…We also showed that commercial kynurenine relaxed pre-constricted arteries, which suggested that kynurenine is an endotheliumderived relaxant factor 6 . Although others have since confirmed these findings 11,12 , we noticed that recently purchased kynurenine no longer caused arterial relaxation, and that HPLC-purified kynurenine and NFK also failed to relax naïve mouse arteries (Fig. 1b).…”
mentioning
confidence: 56%
“…The other data from studies both on animals and patients indicate that KYNA and XA may also have vasorelaxation and antihypertension properties (Figure 1). 143,144,169 These data indicate that the components of the kynurenine pathway can play diverse, sometimes opposite roles in the development of hypertension. Their accumulation in the course of chronic renal failure seems to be at least partly associated with the development of CKD-related hypertension.…”
Section: The Importance Of Accumulation Of the Kynurenine Pathway Commentioning
confidence: 99%
“…They are involved in the pathogenesis of numerous neurodegenerative diseases. 19,29,30,170 Also, the development of chronic renal insufficiency, accompanied by the accumulation of these compounds, is associated with the worsening of neurological disturbances. 29,30,43 Alterations in the TRP, KYN, 3-HKYN, and QA concentrations were observed within CNS homogenates in uremic rats.…”
Section: The Impact Of the Accumulation Of The Kynurenine Pathway Metmentioning
confidence: 99%
“…Notably, however, recent studies have also begun to indicate a physiological role of the metabolite in mammals. Thus, XA, which exhibits antioxidant properties both in vitro and in vivo (Christen et al, 1990, Murakami et al, 2001, Lima et al, 2012), has vasorelaxing properties (Fazio et al, 2017a), attenuates tetrahydrobiopterine biosynthesis (Haruki et al, 2016) and may regulate glucose homeostasis (Favennec et al, 2016). Notably, XA induces apoptotic cell death in cultured lens epithelial cells (Malina et al, 2002) and has been repeatedly linked to various pathological events, including type 2 diabetes (Oxenkrug, 2015).…”
Section: Introductionmentioning
confidence: 99%